A Nonlinear Approach to Quantifying Investor Fear in Stock Markets of BRIC. (17th August 2022) - Asafo-Adjei, Emmanuel; Bossman, Ahmed; Boateng, Ebenezer; Owusu Junior, Peterson; Idun, Anthony Adu-Asare; Agyei, Samuel K.; Adam, Anokye Mohammed
Abstract : The information flow between BRIC and relevant volatilities constitutes a complex network, which needs comprehensive analysis. We provide a rigorous investigation of information flow among stock markets of BRIC and the US VIX in a frequency-domain paradigm. Henceforward, the variation mode decomposition-based entropy approach is employed for the examination of diverse investment horizons and market conditions. First, we find that under stressed market conditions (lower quantiles), significant negative information flow exists between the BRIC constituents and the BRIC composite index. Also, under benign market conditions, we reveal similar dynamics as found at the lower quantiles, which enhances diversification. However, during market booms, we document more positive information flow between the assets and relevant to the redeployment of portfolios. Second, at low probability events representing market stress, we document potential negative information flow amid the stock markets and the US VIX for most investment horizons. Notwithstanding, the US VIX has the potential of transmitting positive information to the stock markets. However, at high market performance, we find more positive information flow amid the BRIC markets and VIX, generally implying long-term efficiency. Investors, portfolio managers, risk managers, and policy-makers should be wary of the heterogeneous and adaptive behaviour of BRIC stock markets with the VIX.